LMNB1/CDKN1A Signaling Regulates the Cell Cycle and Promotes Hepatocellular Carcinoma Progression - Gao, Dute; Guo, Huahu; Liu, Zhaochen; Bao, Liang; Li, Suxin; Wang, Yunchao; Qiu, Jiange; Jiang, Binghua; Dang, Xiaowei (Current cancer drug targets, 2025)
Hepatocellular carcinoma (HCC) is one of the most aggressive malignancies in the world. Lamin B1 (LMNB1) is a key component of the nuclear skeleton structure. Recent studies have found that LMNB1 is overexpressed in tumor tissues and is associated with the prognosis of patients. However, the underlying mechanism remains unclear in HCC. This study aims to explore the clinical significance and molecular mechanisms of LMNB1 in HCC. The expression level of LMNB1 and its clinical values were analyzed with public databases, and the level of LMNB1 in HCC tissues and adjacent normal tissues was confirmed by qRT-PCR and IHC. Functional assays were conducted to explore the impact of LMNB1 knockdown on cell proliferation both and . Additionally, Genes and Genomes enrichment analysis, recovery analysis, and ChIP assays were employed to investigate its underlying molecular mechanisms. Finally, we carried out an analysis of the relationship between LMNB1 and immune cell infiltration in HCC. LMNB1 was found to be overexpressed in HCC and correlated with the pathological stage and unfavorable prognosis. Functional assays demonstrated that LMNB1 promotes HCC proliferation both and . Further analysis revealed that LMNB1 promotes the progression of HCC by regulating CDKN1A expression. Furthermore, the infiltration of immune cells in HCC tissues suggests a potential correlation between immune infiltration cell markers and the expression of LMNB1. LMNB1 emerged as a promising therapeutic target and prognostic biomarker for HCC, with its expression showing a correlation with several immune infiltration cell markers.